Social and Economic Consequences of the Recent Minimum Wage Rise in Lithuania - Karpuškienė, Vita (Ekonomika, 2015)
The government of Lithuania actively increases the minimum wage in 2012–2014: in-one-and-a-half year period it increased by 22 percent – from 246 EUR (850 LTL) to 300 EUR (1035 LTL). It is promised to increase the minimum wage in 2015 as well. The amplification of the competitiveness of the economy is one of the main conditions of economic development. This is emphasized by economists, Lithuanian government, and European Commission. The core issues of the competitiveness of Lithuania are the energy sector and the labour market. Such statement is provided by the European Commission in the 2014 report on Industry competitiveness. Therefore, the aim of this article is to evaluate the economic and social consequences of the increased minimum wage and their impact on the competitiveness of the labour force. In the first part of the article, changes of the minimum wage and their economic and social consequences are analysed. In the rest part of the article, the impact of these consequences on the competitiveness is evaluated.